2019
DOI: 10.1152/ajprenal.00120.2019
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Na+-glucose cotransporter SGLT1 mitigates diabetes-induced upregulation of nitric oxide synthase NOS1 in the macula densa and glomerular hyperfiltration

Abstract: Na+-glucose cotransporter (SGLT)1 mediates glucose reabsorption in late proximal tubules. SGLT1 also mediates macula densa (MD) sensing of an increase in luminal glucose, which increases nitric oxide (NO) synthase 1 (MD-NOS1)-mediated NO formation and potentially glomerular filtratrion rate (GFR). Here, the contribution of SGLT1 was tested by gene knockout (−/−) in type 1 diabetic Akita mice. A low-glucose diet was used to prevent intestinal malabsorption in Sglt1−/− mice and minimize the contribution of intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
3
40
0
Order By: Relevance
“…The hRTE cells were shown to express the SLC5A1 sodium coupled glucose transporter located downstream from the SLC5A2 transporter in the late portion of the proximal tubule. In the kidney, this transporter is only responsible for reabsorbing 3% of filtered glucose [ 35 ]. Our study demonstrated that the expression of SLC5A2 in the human kidney cortex is much higher than the expression in cultured hRTE cells.…”
Section: Discussionmentioning
confidence: 99%
“…The hRTE cells were shown to express the SLC5A1 sodium coupled glucose transporter located downstream from the SLC5A2 transporter in the late portion of the proximal tubule. In the kidney, this transporter is only responsible for reabsorbing 3% of filtered glucose [ 35 ]. Our study demonstrated that the expression of SLC5A2 in the human kidney cortex is much higher than the expression in cultured hRTE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, SGLT2is could inhibit SGLT1 as well as SGLT2 (18,19). Recently, several reports demonstrated the inhibition of SGLT1 could have diuretic effects (16,17). Actually, canagliflozin was reported to be more effective for SGLT1 among the available SGLT2is (24).…”
Section: Respective Data Of Each Parameter At Baseline and 24 Weeksmentioning
confidence: 99%
“…Interestingly, it was reported that the inhibition of sodium glucose transporter-1 (SGLT1) led to same diuretic effect as that of SGLT2 (16,17). It was also reported that SGLT2is could inhibit SGLT1 as well as SGLT2, implying differences in potencies of inhibition of SGLT1 among available SGLT2is (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…47 New studies show knockout of SGLT1 prevents diabetes-induced upregulation of NOS1 in the macula densa and mitigates glomerular hyperfiltration. 48 Absence of SGLT1 also attenuates upregulation of macula densa NOS1 expression in response to SGLT2 inhibition in nondiabetic mice. Furthermore, the effects of SGLT1 and SGLT2 inhibition on diabetic glomerular hyperfiltration were additive.…”
Section: Sglt1 and Macula Densa Signalingmentioning
confidence: 96%